The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/buildings11120622
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Advantages of Modular Construction: Waste Generation

Abstract: The construction industry is a significant source of waste generation in any economy, producing various greenhouse gases, releasing harmful substances into the natural environment, and requiring large areas of land for processing, treatment, and landfilling. The emerging field of off-site prefabrication and assembly is perceived as a viable method to reduce waste and improve sustainability. However, there is a lack of quantifiable research into the difference between off-site prefabrication and on-site, conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Moreover, it improves the social interests of society through improved working conditions. The assembly on the construction site has environmental benefits due to both a significantly shorter and more stable construction process and through a low-waste and low-emission construction site [7]. Economic potentials can be found by the reduced construction time due to the singular assembly of the modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it improves the social interests of society through improved working conditions. The assembly on the construction site has environmental benefits due to both a significantly shorter and more stable construction process and through a low-waste and low-emission construction site [7]. Economic potentials can be found by the reduced construction time due to the singular assembly of the modules.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the repetition effect, the production costs can be recorded more accurate. With a higher degree of prefabrication, the duration of the construction phase can also be reduced, which, among other things, reduces the general construction site costs [7]. The stationary prefabrication of the modules also achieves a better, homogeneous quality.…”
Section: Modular Construction and Its Advantagesmentioning
confidence: 99%
“…-However, this study evaluated only the material production stage and did not perform a comprehensive comparison between the modular method and the traditional RC method. In particular, favorable aspects, such as ease of recycling and reduction of waste, were not considered in the evaluation of modular construction [77]. More meaningful research results will be obtained if economic efficiency and environmental assessment are reevaluated through a full life cycle cost analysis that considers embodied carbon emissions.…”
Section: Safetymentioning
confidence: 99%
“…A similar research analysed and compared the amount of waste generated from modular construction compared to the conventional caste-in-situ construction. The results revealed that 83.2% construction and demolition waste reduction was achieved in the case of modular construction [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%